Electrical product compliance and safety engineering. Volume 2 - Loznen, Steli, 1952-; Bolintineanu, Constantin (Artech House, 2021)
This second volume of an Artech House bestseller presents an enhanced approach toward product compliance and safety engineering. Written by experts in the field, this new volume presents practical material useful for novice and advanced practitioners. & nbsp; Safety aspects of product approvals, energy management, environmental concerns, material science, radiation, hazardous location, and global market access are explored. Practical features related to global market access are presented, including specific documentation and local labeling requirements, as well as language used for safety instructions and user manuals. Compliance and safety aspects of specific applications, such as information technology equipment, audio-video (multimedia), medical, household, alarms systems, luminaires (including LED-lamps) and lamp control, industrial machinery, and semiconductor manufacturing, are discussed. & nbsp; Environmental attributes, including temperature, atmospheric pressure, relative humidity, vibration, shock and packaging/transportation, and how they affect product safety, are analyzed. Information about testing (environmental, HALT, and HASS) is also provided, focusing on the compliance of electrical products with dedicated environmental regulation. Similarities and differences between ATEX and IECEx are defined. Materials, including metal corrosion, adhesives, insulation materials, and information about safety of hazardous materials, are examined.